MENINGKATKAN KEMAMPUAN BERFIKIR LOGIS MATEMATIS MAHASISWA DENGAN MENGGUNAKAN RANGKAIAN LISTRIK PADA MATERI LOGIKA DI IAIN RADEN INTAN LAMPUNG - Netriwati, Netriwati (Al-Jabar: Jurnal Pendidikan Matematika, 2015)
The skill to think logical  match  student in match learing look so low. One of the epport that the author do is to learing electical cicuits in logical material hope can improve skill logic  material by student, and the experience that they get can build their believe about problem that they get and can apply to other that one of clump.            The kind of thorugh is description researcher , data colletion of instrument is interview,supervision dan test result . analysis data used is presentation and average of counting for look raising skill thing logical with data supervision doing question that given.            Based on thorough known that there are increase in the ability think logically and mathematically  result of student learning development using electrical circuits on the material logic in IAIN Raden Intan Lampung.